Dimensions and Evaluation of Social Capital and Its Regional Distribution in the Slovak Republic - Rošková, Ivana; Prochádzková, Martina; Klasová, Slávka; Kováč, Viliam (Italian Sociological Review, 2020)
The paper deals with the dimensions of social capital in the Slovak Republic. The aim is to assess how social capital is distributed socially among the citizens of the Slovak Republic and geographically among the regions of the country. Social capital is evaluated on a basis of the three dimensions, where networks, trust and civism belong. The paper analyses the data from the European Values Study survey, especially the 2008 wave. The results of this study show that social capital has kept a decreasing tendency in the Slovak Republic throughout the period from the year 1991 to the year 2008. The reasons behind this may lie in the historical development of the country – the transformation of the economy and the dissolution of the Czech and Slovak Federative Republic. With respect to a social distribution, social capital is generally higher among more educated, right-wing Slovaks with higher earnings. In the terms of a geographical distribution, the Trnava Region and the Trenčín Region appear to have less developed social capital compared to the other regions in Slovak Republic.